The effect of alumina nanoparticles on the properties of Al-based nanocomposites prepared by powder metallurgy–hot forging - Farah M. Abdul Razzaq; Adnan S. Jabur (International Journal of Lightweight Materials and Manufacture)
The development of the aluminum industry is intricately connected to its special characteristics that have made aluminum a highly desired material in engineering and structural applications. In the present work, the effect of alumina nanoparticle addition on the properties of Al-based nanocomposites was investigated. Al-based nanocomposite samples were fabricated by solid-state route using powder metallurgy and hot forging as a finishing process. The addition of alumina nanoparticles varied from 0 to 10 wt percentage. The structural, mechanical, tribological, and corrosion properties of the prepared Al- nanocomposites samples were studied. It was found that with an increase in the alumina nanoparticles addition up to 10 wt% to the Al-based nanocomposite samples, the hardness and yield strength increased while the reduction percentage, crystallite and grain size decreased. On the other hand, the wear rate decreased up to 5 wt% of addition and then increased again at 10 wt%, but the corrosion rate decreased up to 3 wt% of addition and then increased again up to 10 wt%.